PENGARUH DIMENSI KUALITAS PELAYANAN RITEL TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN SINBUN SIBREH BANDA ACEH - Saed Armia (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2016)
This study examines the factors that affect customer satisfaction in retail stores in Banda Aceh on the purchase of goods and their impact on loyalty. Data collected centrally in the city of Banda Aceh, especially with small retail shops to large traders. The number of respondents surveyed in this study is 100. The research method using Hierarchical Linear Modeling (HLM), the results showed that: 1) the physical aspects of significant effect on customer satisfaction in retail stores in Banda Aceh, 2) Reliability significant effect on customer satisfaction retail stores in Banda Aceh, 3) personal interaction significant effect on customer satisfaction that occurs in retail stores in Banda Aceh, 4) Troubleshooting significant effect on customer satisfaction in retail stores in Banda Aceh, 5) policy significantly influence the intention of customer satisfaction Consumer retail stores in Banda Aceh, 6) Customer satisfaction significant effect on customer loyalty in consumer retail shops in Banda Aceh, 7) physical aspects significant effect on loyalty in mediasikan by customer satisfaction in retail stores in Banda Aceh, 8) Reliability significant effect loyalty mediated by customer satisfaction in retail stores in Banda Aceh, 9) personal interaction significant effect on loyalty mediated by customer satisfaction in retail stores in Banda Aceh, 10) Troubleshooting significant effect on loyalty mediated by customer satisfaction in retail stores Banda Aceh, 11) Policies significant effect on loyalty mediated by customer satisfaction in the consumer retail shops in Banda Aceh.